EFFECT OF NATURAL GROWTH REGULATORY SUBSTANCE (PGR) AND DIFFERENCES OF PLANTING MEDIA ON CHLOROPHIL CONTENT NUMBER OF VEGETABLESTOMATES AND AREA OF VEGETABLESTOMATES MICROGREENS BROCCOLI (Brassica oleracea L.) - Achmad Roihan Roihan (Hasanuddin University, 2021)
Microgreens are plants from the group of vegetables or herbal plants that are harvested at the age of 7-21 days. As a horticultural crop, broccoli (Brassica oleracea L.) is a type of vegetable that belongs to the cabbage family (Brassicaceae). This study aims to determine the effect of natural ZPT and differences in growing media on chlorophyll content, number of stomata and stomata openings of broccoli microgreens. This study consists of 2 treatment factors. The first factor of the planting medium consists of husk charcoal (M1). Cocopeat (M2) and rockwool (M3). The second factor of natural ZPT consists of no ZPT (Z0), coconut water (Z1) and bean sprout extract (Z2). The combination treatment of rockwool growing media and natural zpt of bean sprout extract (M3Z2) gave the best results on parameters of chlorophyll a, b and total content, each of which was 14 days old. While the combination of treatment with cocopeat growing media and natural zpt of bean sprout extract (M1Z2) gave the best results on parameters of chlorophyll a, b and total content, each of which was 21 days after planting. The best parameters for the number of stomata and the area of stomata openings were found in the combination treatment of cocopeat growing media and natural zpt of coconut water (M1Z1), 15.00 and 115.13 μm2, respectively.